Analisis Kehilangan Pangan (Food Loss) Komoditas Beras Di Kalimantan Barat - Ningsih, Febi Purwanti; Maswadi, Maswadi; Kusrini, Novira (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Food loss refers to food that is spilled, spoiled, has an abnormal deterioration in quality such as withering, or is lost before it reaches the consumer. Food loss usually occurs at the stages of production, storage, processing and distribution of the food production chain. Food loss for rice commodities usually occurs during the stages of harvesting, threshing, drying, milling and distribution. This study aims to determine the total estimate and value of food loss losses for rice commodities in West Kalimantan at the stages of harvesting, threshing, drying, milling, and distribution, determine the level of adequacy of rice production in West Kalimantan in meeting the needs of the population, and describe the behavior of farmers in the field. The sample in this study was 50 rice farmers in Sungai Kakap District. The data in this study were processed using Microsoft Excel 2010 and SPSS. The research method used in this study is a quantitative descriptive method. The results of the research show that the estimated total food loss in West Kalimantan is 111.8 tons/year with an estimated value of losses reaching IDR 1,112 trillion/year. Meanwhile, rice production in West Kalimantan tends to be unable to meet the needs of its population both before and after experiencing food loss. However, as many as 38% of farmers have made maximum efforts to reduce food loss in their farming activities